Improvement of Mechanical, Thermal, and Physical Behaviors of Jute/Cotton Biocomposites Reinforced by Spent Tea Leaf Particles - Atiqur, Rahman; Mohammad Asaduzzaman, Chowdhury; Nayem, Hossain; Md. Bengir, Ahmed Shuvho; Md. Arefin, Kowser; Md. Rezaur, Rahman; Muhammad Tariq, Saeed Chani; Kuok King, Kuok; Mohammed M., Rahman (MDPI, 2022)
Natural fibers such as jute, cotton, and bamboo composites are becoming alternative materials to synthetic fiber composites, as their use raises awareness of environmental protection. Among natural fibers, jute and cotton fibers were used in this research to fabricate six-layered composites reinforced by spent tea leaves. Varying amounts (0, 5, 10, and 15 g) of spent tea leaf powder were incorporated as reinforcement with resin to improve and observe properties and determine usability. The prepared composites were investigated comparatively in terms of mechanical, microstructural, morphological, and thermal properties. As regards mechanical characterization, tensile, compression, and bending properties were tested in this research to compare the obtained data with the data available in the literature to show its practical application. The results indicated that significant improvements in mechanical properties were obtained from the composites up to a certain proportion of reinforcement. The addition of 10 g reinforcement of spent tea leaves improved tensile strength by 33.46% and compressive strength by 38.86%. In terms of microstructural, morphological, and thermal characterization, in-depth SEM, EDS, XRD, UV, FTIR, TGA, and DSC analyses were performed. The results revealed that advanced microstructural, morphological, and thermal properties were improved with a certain proportion of spent tea leaf reinforcement.